Välfärdsstatens manifesta och latenta problem med den ökande psykosociala ohälsan i arbetslivet - Michailakis, Dimitris; Schirmer, Werner (Socialvetenskaplig tidskrift, 2016)
The welfare state’s manifest and latent problems with the increasing psychosocial illness in working life This article describes how the debate on psychosocial illness in working life generates manifest and latent problems for the welfare state. Psychosocial illness in working life generates claims and expectations of compensation and interventions directed at the welfare state. Drawing on a systems-theoretical framework, the article argues that the welfare state cannot fulfil these expectations because the enormous complexity and the plurality of factors underlying psychosocial illness makes simple and effective solutions impossible. The causal relations are numerous, diffuse and diffcult to isolate. Next to this manifest problem, the fact that effective regulatory measures are hardly possible creates a latent problem for the welfare state. Despite its powerlessness, the state needs to maintain its self-description as a problem-solving instance. However, the diffuse and ambiguous causal relations underlying psychosocial illness in working life can be transformed into a resource for the welfare state. Precisely this diffuseness and ambiguity increases the discretionary power and capability for action to deal with the claims and expectations of compensation in a way that protects the self-description despite the inability to solve the manifest social problem. If there is a multitude of possible causal explanations depending on how the problem is framed, and given that each causal explanation imposes its own solutions, the state can treat the ambiguous causalities that research findings offer as a smorgasbord for its own purposes. The state can choose among the causes those interventions that seem most appropriate to solve the latent problem: the protection of the welfare state’s self-description as a problem-solving, caring institution with capability for action. Because the argument is complex, the article provides a detailed introduction of the systems-theoretical concepts. Furthermore, the argument is illustrated with the help of the case of the working milieu of school in suburbs with high degrees of ethnic diversity.